Bone mineral density in male weight-classified athletes is higher than that in male endurance-athletes and non-athletes - Sagayama, H.; Kondo, E.; Tanabe,Y.; Ohnishi, T.; Yamada, Y.; Takahashi, H. (Clinical Nutrition, 2020)
Background